Um lugar que passa e sobrevive:o passado e o presente na Vila de Ponta Negra - Silva, Maria Suely Paula da (2006)
The Ponta Negra borough is a part and the originally core of Ponta Negra quarter, placed on the South area of Natal/RN city. Its population was constituted by fishermen whose, beyond the fishing work, cultivated small plantations, made carbon and lace. For a long period of time, the borough was isolated from the rest of the city because of the great ground distance and due the fact that the local inhabitants found their own maintenance on the place. The scenery was being little by little modified from de 80 s because of the neighborhood urban development, that became one of the most searching tourism places in the city that turns the borough into a expensive place to live, with plenty of entertainment and high income, due the new habitation standards, new economic activities, new inhabitants belonging to higher social classes, new habits and way of living. The present work aims to verify weather or not, in the middle of all changes, the original social actors that still live in the Ponta Negra borough, are able to keep the traditional community bounds that once guided their existences. On that sense, we will analyze the conflicts that pass through the community, with attention on the sociability, space usage and appropriation